2008
DOI: 10.1159/000170902
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Clinical Significance of Hepatitis B Virus Genotypes, Core Promoter and Precore Mutations in Eastern India

Abstract: Objectives: This unmatched case-control study aimed at determining the molecular epidemiology and clinical significance of HBV genotypes, core promoter (CP) and precore (PC) mutations in Eastern India. Methods: Serological, biochemical and molecular assays were used to examine antigens, ALT, genotypes, mutations and viremia among 106 inactive carriers and 183 chronic liver disease (CLD) patients. Results: Male gender (p < 0.001), HBeAg positivity (p = 0.050), high ALT (p < 0.001), high viremia (p < 0.001), CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 122 publications
5
26
0
Order By: Relevance
“…Recent studies also have shown the differential clinical/virological significance of different HBV genotypes (13,34,47). The present study offers further evidence in favor of the differential clinical implications of HBV genetic variability in terms of the evolution of immune escape variants and compartmentalization.…”
Section: Discussionsupporting
confidence: 66%
“…Recent studies also have shown the differential clinical/virological significance of different HBV genotypes (13,34,47). The present study offers further evidence in favor of the differential clinical implications of HBV genetic variability in terms of the evolution of immune escape variants and compartmentalization.…”
Section: Discussionsupporting
confidence: 66%
“…In our study, BCP mutation was found in 29.1% of patients with genotype D, which was significantly more than in genotype A (17.7%, P = 0.001). A study from eastern India reported an association of the BCP mutation with the HBV genotypes A and C [30], while another study by Chauhan et al concluded that the BCP mutations were similarly present in all genotypes [31].…”
Section: Discussionmentioning
confidence: 98%
“…This is in accordance with studies from India and rest of the world. 15,17,18 PC (A1896) and BCP (T1762 and A1764) are the most common and clinically significant mutations in the precore/core region. Prevalence of basal core promoter and precore mutants in precore/core region ranging from 33 to 37% has been reported in India amongst chronic HBV patients.…”
Section: Hbv Genotypementioning
confidence: 99%